Creativity to Draw Illustration Using Montage Techniques in Grade VIII Students in SMP Muhammadyah 1 Kudus - Surya Adi, Adinda; Syakir, Syakir; Sugiarto, Eko (Universitas Negeri Semarang, 2019)
Learning art at the high school level is an important part of the formal school learning process. Art education and creativity through the art of illustration in the process of learning in SMP Muhammadiyah 1 Kudus is an aesthetic educational institution for learners. An introduction to the values ​​of working with illustrative art, the sensitivity of elements and principles of evaluation of illustrative artwork and the importance of creativity education to students through the techniques of montage in illustrative artwork. This research used qualitative descriptive methods. With the study setting in the SMP Muhammadiyah 1 Kudus in Class VIII-H. Data collection techniques are interviews, observations and documentation. Data analysis using qualitative research stages and validity of data using Triangulation data. The results of the research are revealing; (1) the process of implementing illustrative art learning with the application of montage techniques to the grade VIII students of SMP Muhammadiyah 1 Kudus, (2) the analysis of art elements and design principles in the aesthetic assessment of 12 illustrated works of art, and (3) the analysis of creative creativity art works of 12 illustrated works using montage techniques. The conclusion from the analysis of the 12 paintings, shows that the art of illustration with the montage technique is a form of aesthetic expression and artistic creativity from the expression of the ideas and ideas of each student in the art of assessment of elements and principles of art.